Nutritional quality of indigenous legume browse in southern Ethiopia: farmers’ preference and correlation of local valuation of feed value with scientific indicators - Abraham, Getachew; Kechero, Yisehak; Andualem, Dereje (Frontiers in Veterinary Science, 2023)
The research was carried out in southern Ethiopia to determine farmers' preferences for indigenous legumes, fodder trees, and shrubs (ILFTS), as well as the relationship between farmer feed valuation and scientific parameters. A focus group discussion (FGD) was conducted with ten farmers in each agroecological zone to determine the benchmarks for the preference ratings. The respondent farmers used the preference score sheet to rate all ILFTS on an individual basis. Twenty farmers with extensive experience in ILFTS took part in the preference score rating of each plant species in each agroecosystems. Dry matter (DM), organic matter (OM), ash, crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), acid detergent lignin (ADL), metabolizable energy (ME) and condensed tannin (CT) content of the samples were determined. The standard two-stage in vitro Tilley and Terry method was used to measure the in vitro dry matter digestibility (IVDMD) and in vitro organic matter digestibility (IVOMD) of samples. Digestible organic matter in dry matter (DOMD) and ME values were estimated using standard models. Analysis of variance (ANOVA) was used to analyze the variation among the species in agroecosystems. Tukey HSD tests were used for mean separation.preference score on the evaluation criteria differed considerably (P<0.05) with species in agroecosystems. The CP, ash, and ME values of ILFTS in the study were moderate to high although exhibited a wide variation among the species in agroecosystems. The CP content was above the minimum requirement (8%) to support the normal function of rumen microorganisms. Moreover, CP content exhibited a positive significant correlation with IVDMD, IVOMD, and DOMD, unlike CT and ADL which exhibited a negative significant correlation. Conversely, the DM, OM, CP, IVDMD, IVOMD, DOMD, and ME were shown a positive significant correlation with farmers' feed value preference score, unlike the ADL and CT which exhibited a negative significant correlation. In conclusion, Farmers' indigenous knowledge of feed value is therefore relevant for judging the nutritive value of the ILFTS and could complement the scientific indicators.